Spinal meningiomas – Risks and potential of an increasing age at the time of surgery. (November 2018) - Schwake, Michael; Adeli, Alborz; Sporns, Peter; Ewelt, Christian; Schmitz, Thorsten; Sicking, Johanna; Hess, Katharina; Cäcilia Spille, Dorothee; Paulus, Werner; Stummer, Walter; Brokinkel, Benjamin
Highlights: Patients' age is not associated with tumor location or volume in spinal meningiomas. Risk of preoperative motor and sensory deficits rises with age at diagnosis. Surgical procedures do not correlate with patients' age. Non-neurological complications are common in elderly patients. Increasing age is associated with postoperative symptom improvement. Abstract: Although the majority of surgeries for spinal meningiomas are performed in geriatric patients, age-related analyzes of preoperative symptoms and functional outcome are sparse. Clinical, neuropathological and radiological data of 88 patients who underwent surgery for spinal meningiomas were reviewed. Correlations between the patients' age and preoperative symptoms as well as functional outcome were investigated. 14 males (16%) and 74 females (84%) with a median age of 67 years were included. Age at the time of surgery was independent of the tumor location and volume, intra-/extradural tumor location, spinal cord compression or signal change on T2-weighted MRI (p > 0.05, each). Preoperative McCormick score (p = 0.001), motor (p = 0.005) and sensory (p = 0.025) deficits and incontinence (p = 0.010) increased, while frequency of radicular pain decreased with increasing age (p = 0.020). Multivariate analyses confirmed an increasing risk of motor (OR: 1.05, p = 0.017) and, with borderline significance, of sensory deficits (OR: 1.04, 95%CI 1.00–1.10; p = 0.056) with rising age. Simpson grades I, II, III and IV were achieved in 12 (14%), 54 (64%), 14 (17%) and 4 (5%) individuals, respectively. Only 3 of 12 patients (25%) with perioperative complications were younger than 65 years. Rising age was associated with improvement of motor (p = 0.006) and sensory deficits (p = 0.045). In multivariate analyzes, probability of improvement of preoperative motor weakness (OR = 1.05, p = 0.031) and sensory deficits (OR = 1.07, p = 0.014) increased with rising age. Despite more frequent preoperative neurological deficits, older patients with spinal meningiomas recover most noticeably after surgery. However, stratification of the medical condition is urgent to reduce complications.